Moderation and revolution - Micocci, Andrea (Lexington Books, 2012)
In the intellectuality of capitalism there are two alternative ways to conceive of reality: the moderate one, which mediates dialectically, and the revolutionary one, which also comprises ruptures with disappearance. The former conforms to, and helps shape, the metaphysics of capitalism itself. The second is akin to the mode of progressing of nature in general, and forms the basis for materialism. Moderate positions tend to be intolerant because they do not recognize the other, which is constantly compelled to mediate. Revolutionary positions instead, recognizing the other, are tolerant and in.